2020
DOI: 10.1002/hbm.25236
|View full text |Cite
|
Sign up to set email alerts
|

Mediofrontal theta‐band oscillations reflect top‐down influence in the ventriloquist illusion

Abstract: In the ventriloquist illusion, spatially disparate visual signals can influence the perceived location of simultaneous sounds. Previous studies have shown asymmetrical responses in auditory cortical regions following perceived peripheral sound shifts. Moreover, higher-order cortical areas perform inferences on the sources of disparate audiovisual signals. Recent studies have also highlighted top-down influence in the ventriloquist illusion and postulated a governing function of neural oscillations for crossmod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Other studies have also investigated theta power in other aspects of multisensory processing. For example, an EEG ventriloquism study found lower pre-stimulus theta power in trials in which participants experienced the illusion versus trials in which they did not [ 60 ]. This result does not necessarily go in opposition to ours, as it explored the pre-stimulus period, instead of post-stimulus induced activity.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also investigated theta power in other aspects of multisensory processing. For example, an EEG ventriloquism study found lower pre-stimulus theta power in trials in which participants experienced the illusion versus trials in which they did not [ 60 ]. This result does not necessarily go in opposition to ours, as it explored the pre-stimulus period, instead of post-stimulus induced activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in terms of the theta band, while the current review focused on theta generation in areas such as the hippocampus and PFC during memory processes, recent research has implicated theta as a mechanism in top-down processing from the mediofrontal cortex during multimodal processing during phenomena such as the ventriloquist illusion. 141 Moreover, the interaction of theta and gamma oscillations (eg, thetagamma coupling) my play a key role in visual selective and sustained attention. 142,143 In this context, low-frequency oscillations in the theta range may play a crucial role in bringing together local information processing by neurons engaged in high-frequency oscillatory activity in the gamma range.…”
Section: Cannabinoids and Neural Oscillations: Clinical Implications ...mentioning
confidence: 99%
“…We here address this question using the spatial ventriloquism paradigm as a model (Bertelson et al, 2000;Bruns, 2019;Bruns et al, 2014;Howard & Templeton, 1966;Kaiser et al, 2021). Across four experiments, we asked how two visual signals are combined with one sound to shape judgements about the sound's location.…”
mentioning
confidence: 99%